Serum level of il-6 in patients of type-ii diabetes mellitus with and without retinopathy: a comparative study (Bangladesh Journal of Medical Science, 2017)
Aim: Pakistan has 6.9 million people with diabetes mellitus (DM) that will be doubled by 2025. A study was designed to determine serum levels of IL-6 in type 2 diabetes mellitus (T2DM) patients.Methods: It was a cross-sectional case-control study of 212 subjects. Group-I included 30 subjects without DM, Group-II had 30 T2DM without retinopathy and Group-III had 152 T2DM with retinopathy. IL-6 was determined by ELISA technique. Data was analysed using SPSS 17.0.Results: More females were in Group-II (83%) and Group-III (66%) compared to Group-I (30%). Higher age was in Group-II (49yrs) and Group-III (50yrs) compared to Group-I (34yrs). Mean duration of disease (in years) was more in Group-III (10.51) than Group-II (7.76). Highest mean level of IL-6 was in Group-II, followed by Group-I and Group-III. On comparison, gender, age, duration of disease and the level of IL-6, there was a significant difference while there was no significant difference between percentages of HbA1c. The logistic regression model suggested low levels of IL-6 in patients of diabetic retinopathy was an independent predictor of retinopathy in patients with T2DM.Conclusion: Serum level of IL-6 was low in patients of diabetic retinopathopathy as compared to patients with T2DM without retinopathy.Bangladesh Journal of Medical Science Vol.16(4) 2017 p.525-529